Simplifying
102 = 69 + -7x + 3x
Combine like terms: -7x + 3x = -4x
102 = 69 + -4x
Solving
102 = 69 + -4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '4x' to each side of the equation.
102 + 4x = 69 + -4x + 4x
Combine like terms: -4x + 4x = 0
102 + 4x = 69 + 0
102 + 4x = 69
Add '-102' to each side of the equation.
102 + -102 + 4x = 69 + -102
Combine like terms: 102 + -102 = 0
0 + 4x = 69 + -102
4x = 69 + -102
Combine like terms: 69 + -102 = -33
4x = -33
Divide each side by '4'.
x = -8.25
Simplifying
x = -8.25